(untitled) (INNOVATIVE ECONOMY, 2023)
Yurkevych H.Y. MODELLING THE PSYCHO-INFORMATIONAL STRUCTURE OF THE GROUP Purpose. The aim of the article is to substantiate the need to model the psycho-informational structure of the group for effective professional activity. Methodology of research. Achieving the goal and solving the tasks of our research involves the use of a number of methods of theoretical scientific research: historical, analysis, abstract and logical – to establish the essence and tasks of generalizing the conceptual foundations of the psychological aspects of the information structure of the psyche of the individual, as well as revealing the relationship between psychotype and the success of the organization; interpretations and comparisons – to determine the perspectives of modelling the psycho-informational structure of the group; inductions and deductions – when determining the influence of the competence of employees in the organization for effective professional activity; generalization – for formulating one’s own interpretation of the applied role of psycho-informatics and the conclusions of the conducted research. Findings. The individual psychological features of a person are revealed and their interrelationships in a group are defined in the paradigm of socio-humanitarian problems of society. It was determined that in order to build an ideal model of the organization, it is necessary to observe the main system principles or features of the organization, namely, purposefulness, functionality, specialization, competence, integrity. The role and place of the psycho-informational structure of the group is substantiated. Originality. As a result of the study, approaches to developing an informational model of the psyche for each of the psycho-types of employees by the manager to change “imperfect” people into a real “perfect” organization and achieve the effectiveness and stability of the organization were further developed. Practical value. The proposals substantiated by the results of the research provide an opportunity to model the psycho-informational structure of the group for the competent performance of their work in the organization of any form of ownership, regardless of the sphere of business and branch affiliation. Key words: socionics, socionic type, information flow, psycho-informational body, types of information influences, socionic function, psycho-informatics.